Articulated robot arm - Mohamad Hafiz, Mohd Fauzi; Ismail, Mohd Khairuddin; Anwar P. P., Abdul Majeed; Mohd Azraai, Mohd Razman; Wan Hasbullah, Mohd Isa (Penerbit UMP, 2021)
In medical rehabilitation programs, trajectory tracking is used to increase the repeatability of joint movement and the patient's recovery in the early phases of rehabilitation. In order to achieve that, the robotic arm has been implemented since it can provide a precise and move in almost perfect motion. This manuscript aim to develop and simulate a 2DOF robotic arn that will able to tracking the trajectory successfully. Hence, in order to achieved that a modeling, simulation, and control of a Two Degree of Freedom (2-DOF) Robot Arm is being discussed in this manuscript. First, the robot specifications, as well as Robot Kinematics forward and inverse kinematics of a 2-DOF robot arm, are provided. The dynamics of the 2-DOF robot arm were then formulated in order to obtain motion equations by using the Eular-Lagrange Equation. For the controller of the robot, a control design was created utilising a PID controller. All the data is recorded from the margin of error as well as the overshoot and peak settling time is being record via matlab. The data is differentiate by with with controller, with PI and PID, in which the error is less than 12.5 and 1.63 consecutively. The data that being gathered show that a controller best suited in this rehabilitation robot